2021
DOI: 10.4103/ijo.ijo_2235_21
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-associated optic neuritis – A case series and review of literature

Abstract: Neuroophthalmic manifestations are very rare in corona virus disease-19 (COVID-19) infection. Only few reports have been published till date describing COVID-19-associated neuroophthalmic manifestations. We, hereby, present a series of three cases who developed optic neuritis during the recovery period from COVID-19 infection. Among the three patients, demyelinating lesions were identified in two cases, while another case was associated with serum antibodies against myelin oligodendrocyte glycoprotein. All thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Several rare manifestations of COVID‐19 have been reported in the literature, with these manifestations including seizures and status epilepticus (Asadi‐Pooya et al, 2021), meningoencephalitis (Oosthuizen et al, 2021), Guillain–Barré syndrome (Toscano et al, 2020), acute necrotizing encephalopathy (Geng et al, 2023), and multisystem inflammatory syndrome in children (Whittaker et al, 2020). In addition, myositis (Saud et al, 2021), catatonia (Anvekar et al, 2022), vasculitis and arthritis (Batu et al, 2022), optic neuritis (Jossy et al, 2022), dermatological manifestations (Lipsker, 2020; Marraha et al, 2020), conjunctivitis (Danthuluri & Grant, 2020), and endocrine and metabolic complications (Esmaeilzadeh et al, 2022) have been observed. Some of these rare manifestations might be associated with a poor prognosis.…”
Section: Brief Review Of Coronavirus 2019mentioning
confidence: 99%
“…Several rare manifestations of COVID‐19 have been reported in the literature, with these manifestations including seizures and status epilepticus (Asadi‐Pooya et al, 2021), meningoencephalitis (Oosthuizen et al, 2021), Guillain–Barré syndrome (Toscano et al, 2020), acute necrotizing encephalopathy (Geng et al, 2023), and multisystem inflammatory syndrome in children (Whittaker et al, 2020). In addition, myositis (Saud et al, 2021), catatonia (Anvekar et al, 2022), vasculitis and arthritis (Batu et al, 2022), optic neuritis (Jossy et al, 2022), dermatological manifestations (Lipsker, 2020; Marraha et al, 2020), conjunctivitis (Danthuluri & Grant, 2020), and endocrine and metabolic complications (Esmaeilzadeh et al, 2022) have been observed. Some of these rare manifestations might be associated with a poor prognosis.…”
Section: Brief Review Of Coronavirus 2019mentioning
confidence: 99%
“…In addition, because D-dimer and erythrocyte sedimentation rates (ESR) were the only laboratory parameters that were higher in these patients compared with controls, the authors concluded that ocular comorbidities could be related to systemic inflammation related to SARS-CoV-2 infection, particularly coagulation alterations. Jossy et al [ 84 ] described three patients who developed optic neuritis while recovering from COVID-19 infection. One was positive for serum antigens.…”
Section: Long-covid Neurological and Psychological Symptomsmentioning
confidence: 99%
“…Optic neuritis (ON) induced by COVID‐19 is a very rare manifestation that sometimes causes relapsing inflammatory optic neuropathy. Several studies have shown that patients with COVID‐19‐induced ON have a good visual recovery (Josy et al., 2022; Sawalha et al., 2020). However, these scattered reports do not give us a systematic understanding of first‐episode ON after COVID‐19.…”
Section: Figurementioning
confidence: 99%